2011
DOI: 10.1002/jlcr.1950
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale preparation and labelling reactions of deuterated silanes

Abstract: A catalytic synthesis of deuterated silanes SiEt 3 D, SiMe 2 PhD and SiPh 2 D 2 is reported that allows their facile generation in a 3-4 g scale, utilizing D 2 (0.5 bar) as the hydrogen isotope source and low catalyst loadings (0.01 mol%). The catalyst precursor is the rhodium (III) complex 1, which contains a (h 5 -C 5 Me 5 )Rh cation stabilized by coordination to a cyclometallated phoshine PMeXyl 2 (Xyl = 2,6-C 6 H 3 Me 2 ). The same complex is also an active catalyst for the hydrosilylation of the C= =O and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…We have also examined other relevant applications, such as catalytic hydrogen‐isotope exchange, hydrosilylation of carbonyl groups and other unsaturated functionalities, as well as the formation of CC bonds 5d. 8ab, 11, 12 Related complexes that accommodate N^N or N^C mono‐anionic ligands, rather than P^C ligands, also display rich and versatile chemistry 1. 2, 6…”
Section: Introductionmentioning
confidence: 99%
“…We have also examined other relevant applications, such as catalytic hydrogen‐isotope exchange, hydrosilylation of carbonyl groups and other unsaturated functionalities, as well as the formation of CC bonds 5d. 8ab, 11, 12 Related complexes that accommodate N^N or N^C mono‐anionic ligands, rather than P^C ligands, also display rich and versatile chemistry 1. 2, 6…”
Section: Introductionmentioning
confidence: 99%
“…The studies of silane deuteration reported by Carmona, and Nolan have featured expensive air‐sensitive rhodium‐ or iridium‐ligand complexes as catalysts 9a,b,10. In our system, even if ruthenium can be considered as a cheaper metal, we are still faced with the sensitivity problem of 1 and 2 .…”
Section: Methodsmentioning
confidence: 96%
“…Rhodium-catalyzed hydrosilylation of α,β-unsaturated nitriles into vinylamines was achieved by Carmona’s group in 2011 (Scheme 4) [24]. Acetonitrile showed low activity (<40%) and benzonitrile did not undergo hydrosilylation in this catalytic system.…”
Section: Double Hydrosilylation Of Organonitrilesmentioning
confidence: 99%
“…However, these hydrometalations do not occur under typical reaction conditions for hydrosilylation [14] and hydroborylation [15] because of the strong C≡N bond dissociation energy (179.3 kcal/mol, 750.0 kJ/mol) [16]. Actually, examples of catalytic double hydrometalation of the carbon-nitrogen triple bond (C≡N bond) in organonitriles are limited: one example of Fe [12], Pt [17], Ir [18], and Ru [19], two examples of Co [20,21], four examples of Rh [22,23,24,25], and main group elements and fluoride [13,26,27,28] for double hydrosilylation and one example of Mg [29], Co [30], and Ni [31], and two examples of Ru [32,33] and Mo [34,35] for double hydroborylation have been reported to date. Those metal catalysts are depicted in Figure 1.…”
Section: Introductionmentioning
confidence: 99%